Labor and puerperium outcomes in women with a history of urinary tract infection during pregnancy - Paes, Bruna Thais da Rocha; Sales, Ana Paula de Assis; Madeiro, Vivian Maria; de Souza, Tailma Silva Lino; Brito, Gabrielly Segatto; Maciel, Juscilene da Silva; Campos, Laís Flávia de Castro Pinheiro; Soldera, Andrezza Gabrielly dos Santos; dos Santos, Andriely Gomes (Seven Editora, 2024)
Objective: To summarize the studies that evaluate possible outcomes of labor and puerperium in women who had Urinary Tract Infection during pregnancy. Methods: Integrative literature review with a search carried out in the Virtual Health Library (VHL), National Library of Medicine National Institutes of Health (PubMed), Web of Science and CINAHL databases, with articles from 2018 to 2022 as inclusion criteria. Results: Seven articles were selected for this review, and all studies brought preterm labor as one of the main outcomes, followed by 71.4% that point to low birth weight, 42.9% emphasize neonatal death, 28.6% point to abortion and premature rupture of membranes, 14.3% associate neonatal asphyxia and preeclampsia as one of the main findings. In addition, 42.9% of the articles outlined the sociodemographic profile of these women, relating maternal age, multiparity, ethnicity, and socioeconomic conditions. Conclusion: Prematurity, low birth weight, and neonatal death were the main outcomes found in this review. It is suggested that further studies investigate whether there is a relationship between neonatal asphyxia and preeclampsia as complications of UTI in pregnancy. DOI:https://doi.org/10.56238/sevened2024.016-003